Pyrazoline Derivatives: Potential Therapeutic Agents against Parkinson's disease - Bidhyut Kumar Dubey; Jyoti Anurag; Avinash Chandra Tripathi; Mohini Chaurasia; Mohammad Asif, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Parkinson's disease (PD) is a neurodegenerative disorder that results in the gradual death of dopaminergic neurons in the human brain, leading to both motor impairment and a variety of non-motor symptoms. Pyrazoline is a heterocyclic compound known for its pharmacological spectrum and anti-inflammatory, antioxidant, and neuroprotective properties. Recent studies have highlighted its potential in modulating key pathways involved in PD, such as oxidative stress, mitochondrial dysfunction, and neuroinflammation, all of which are central to the progression of Parkinson's disease. These derivatives have shown promise in preclinical models by mitigating neuronal damage and preserving motor function, making them attractive candidates for further research. This review included the background on Parkinson’s disease, current treatment options, common synthetic route of Pyrazoline ring, current medicines used for the treatment of PD, and recent studies done on Pyrazoline ring as anti-Parkinson's.